The effect of different rations on the development of ciliate protozoa in the rumen of angora goats - Mehmet Kocabatmaz; Mursayettin Eksen; Zafer Durgun (Eurasian Journal of Veterinary Sciences)
In this investigation pH values, protozoa counts, protozoa volumes and protozoa species were determined in the rumen contents of Angora goats fed with different rations. For this purpose 4 animals with 2 years old and with permanent rumen cannula were used.